INTERVENSI ORIENTASI REALITA PADA PASIEN SKIZOFRENIA DENGAN DIAGNOSIS KEPERAWATAN GANGGUAN PROSES PIKIR DI RUANG KAKA TUA RUMAH SAKIT JIWA DR. RADJIMAN WEDIODININGRAT LAWANG - Nuzulul Rizqi Hamdani; Indari; Juliati Koesrini (Jurnal Riset Multidisiplin Edukasi, 2026)
Schizophrenia is a severe mental disorder characterized by disturbances in thought processes, including grandiose delusions that affect social functioning and patient behavior. Reality Orientation Therapy (ROT) is a nursing intervention that helps patients recognize reality through therapeutic communication. This scientific paper aims to describe the implementation of Reality Orientation Therapy in patients with schizophrenia with the nursing diagnosis of disturbed thought processes: grandiose delusions in the Kaka Tua Ward of Dr. Radjiman Wediodiningrat Mental Hospital, Lawang. The study used a descriptive design with a case report approach involving two patients with schizophrenia. Data were collected through interviews, observation, mental status examinations, and medical record documentation. Interventions included orientation to person, place, and time, establishing a therapeutic relationship, medication adherence education, and family involvement. The results showed decreased delusional verbalization and improved reality orientation, communication, and concentration. Reality Orientation Therapy is effective in helping control disturbed thought processes in patients with schizophrenia experiencing grandiose delusions.